Newspaper Reading Patterns in the Era of Social Media Among Mass Communication Students of Chukwu Odumegwu Ojukwu University (COOU) Igbariam, Anambra State - Shadrach, Idi; Adikuru, Chinonso Chinaemerem; Yerima, Abel (Darul Yasin Al Sys, 2025)
This study investigates the newspaper reading patterns of Mass Communication students at Chukwu Odumegwu Ojukwu University (COOU), Igbariam, with particular emphasis on frequency of readership, gratifications sought, preferred formats, and the influence of social media on newspaper consumption. Employing a descriptive survey research design, data were collected from a sample of 192 students using a structured online questionnaire. The findings reveal that newspaper readership among the students is generally infrequent, with most respondents engaging in occasional reading of traditional print newspapers. Key motivations for newspaper consumption include entertainment, relaxation, and the desire to stay informed. However, a notable shift toward online newspaper formats was observed, driven by factors such as convenience, accessibility, and ease of navigation. The study also establishes that social media platforms significantly influence students' information-seeking behavior, often serving as alternatives to traditional and online newspapers. These trends suggest a growing reliance on digital platforms for news consumption among university students. In light of these findings, the study recommends that newspaper publishers adopt integrated social media strategies to strengthen their digital presence, diversify content to address both entertainment and in-depth news preferences, and that communication curricula be enhanced with media literacy components to foster critical engagement with news content across platforms. Keywords: Newspaper Readership; Social Media Influence; Digital News Consumption; Mass Communication Students; Media Literacy